Fish Bone Migration- Culprit Leading to RetroParaoesophageal Abscess, Mediastinitis and Vocal Cord Palsy - M, Paul; M, Shashigopalan; NWS, Johnson (IIUM Medical Journal Malaysia, 2019)
Fish bone ingestion and impaction are known to everyone. However, such benign incidences have been reported to be associated with multiple potentially life threatening complications. Anatomical features of the oesophagus forms the basis for such incidences. We report here an elderly diabetic gentleman with an unusual left retro-paraoesophageal abscess complicated with oesophageal perforation, mediastinitis and vocal cord paresis which were fundamentally caused by a migrated fish bone into the lower part of the neck requiring therapeutic external neck exploration. Management of this case and its complications are described here comprehensively.